Ni-based SBA-15 catalysts modified with CeMnOx for CO2 valorization via dry reforming of methane: Effect of composition on modulating activity and H2/CO ratio - Grabchenko, Maria V.; Dorofeeva, Nataliya V.; Svetlichnyi, Valerii A.; Larichev, Yurii V.; La Parola, Valeria; Liotta, Leonarda Francesca; Kulinich, Sergei A.; Vodyankina, Olga V. (Nanomaterials)
Dry reforming of methane with ratio CH4/CO2 = 1 is studied using supported Ni catalysts on SBA-15 modified by CeMnOx mixed oxides with different Ce/Mn ratios (0.25, 1 and 9). The obtained samples are characterized by wide-angle XRD, SAXS, N2 sorption, TPR-H2, TEM, UV–vis and Raman spectroscopies. The SBA-15 modification with CeMnOx decreases the sizes of NiO nanoparticles and enhances the NiO–support interaction. When Ce/Mn = 9, the NiO forms small particles on the surface of large CeO2 particles and/or interacts with CeO2, forming mixed phases. The best catalytic performance (at 650 C, CH4 and CO2 conversions are 51 and 69%, respectively) is achieved over the Ni/CeMnOx/SBA-15 (9:1) catalyst. The peculiar CeMnOx composition (Ce/Mn = 9) also improves the catalyst stability: In a 24 h stability test, the CH4 conversion decreases by 18 rel.% as compared to a 30 rel.% decrease for unmodified catalyst. The enhanced catalytic stability of Ni/CeMnOx/SBA-15 (9:1) is attributed to the high concentration of reactive peroxo (O-) and superoxo (O2-) species that significantly lower the amount of coke in comparison with Ni-SBA-15 unmodified catalyst (weight loss of 2.7% vs. 42.2%). Ni-SBA-15 modified with equimolar Ce/Mn ratio or Mn excess is less performing. Ni/CeMnOx/SBA-15 (1:4) with the highest content of manganese shows the minimum conversions of reagents in the entire temperature range (X(CO2) = 4–36%, X(CH4) = 8–58%). This finding is possibly attributed to the presence of manganese oxide, which decorates the Ni particles due to its redistribution at the preparation stage.